Conférence: «Travail et santé au travail des femmes en contexte de pandémie» (2020)
La pandémie de COVID-19 a mis en lumière combien les femmes étaient en première ligne dans le système hospitalier et dans les soins aux personnes âgées au Québec. En d’autres mots : la pandémie a révélé l’importance de nombreux métiers mal rémunérés et souvent négligés, dont on se soucie peu, qui sont occupés à 80% par des femmes.
Keywords: 2000 à aujourd'hui; amériques; covid-19; femmes*; pandémie; personnes âgées; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques; travail; travail des femmes*

Kuei, je te salue: conversation sur le racisme - Béchard, Deni Ellis; Kanapé Fontaine, Natasha (Éditions Écosociété, 2020)
« En 2016, la poète lnnu Natasha Kanapé Fontaine et le romancier québéco-américain Deni Ellis Béchard entamaient une conversation sans tabou sur le racisme entre Autochtones et Allochtones. Comment cohabiter si notre histoire commune est empreinte de honte, de blessures et de colère? Comment faire réaliser aux Blancs le privilège invisible de la domination historique? Comment guérir les Autochtones des stigmates du génocide culturel? Ces questions traversent leurs échanges: Natasha raconte sa découverte des pensionnats autochtones, son obsession pour la crise d'Oka, la vie dans la communauté de Pessamit ; Deni parle du racisme ordinaire de son père, de la ségrégation envers les Afro-Américains, de son identité de Québécois aux États-Unis. Cinq ans plus tard, Deni et Natasha reprennent la plume pour poursuivre ce "rendez-vous de la parole qui s'ouvre". Renouant avec le ton intimiste et le foisonnement intellectuel de leur premier échange, ils abordent des sujets d'une brûlante actualité: mobilisation de Black Lives Matter après la mort de George Floyd, feux de forêt en Californie, campagne présidentielle sur fond de montée de l'intolérance; soulèvement des Wet'suwet'en et blocus ferroviaires, dénonciation de la politique de la reconnaissance du gouvernement Trudeau. Puis survient l'impensable: Joyce Echaquan, une Atikamekw de 37 ans, meurt sous les injures racistes de deux infirmières de l'hôpital de Joliette. Une vague d'indignation monte ...»–Quatrième de couverture.
Section: 203 pages ; 22 cm.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; histoire et politique; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; santé; système colonial; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

Femmes et Environnement. Enjeux d'égalité pour toutes les femmes - Boivin, Martine (Le Réseau des Tables régionales de groupes de femmes du Québec, 2020)
Le Réseau des Tables régionales de groupes de femmes du Québec est un regroupement provincial composé des 17 Tables régionales de groupes de femmes au Québec. Il s’agit d’un regroupement féministe de défense collective des droits, qui travaille sur les questions mettant en jeu les intérêts et les droits des femmes. La spécificité du regroupement est représentée par l’expertise régionale développée par les Tables régionales dans les dossiers de la condition féminine. Porte-voix des régions auprès des instances nationales, le RTRGFQ favorise la prise de parole collective des Tables régionales, tout en respectant leurs particularités. Le RTRGFQ et les Tables régionales sont en action depuis plus de 20 ans pour favoriser la participation des femmes à la vie démocratique québécoise
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; charge mentale; charge émotionnelle; environnement; intersectionnalité; projet charge mentale; périodes historiques; québec; ressource en ligne; régions géographiques; santé; thématiques

Menstruation: Science and society - Critchley, Hilary O. D.; Babayev, Elnur; Bulun, Serdar E.; Clark, Sandy; Garcia-Grau, Iolanda; Gregersen, Peter K.; Kilcoyne, Aoife; Kim, Ji-Yong Julie; Lavender, Missy; Marsh, Erica E.; Matteson, Kristen A.; Maybin, Jacqueline A.; et al. (American Journal of Obstetrics and Gynecology, 2020)
Women's health concerns are generally underrepresented in basic and translational research, but reproductive health in particular has been hampered by a lack of understanding of basic uterine and menstrual physiology. Menstrual health is an integral part of overall health because between menarche and menopause, most women menstruate. Yet for tens of millions of women around the world, menstruation regularly and often catastrophically disrupts their physical, mental, and social well-being. Enhancing our understanding of the underlying phenomena involved in menstruation, abnormal uterine bleeding, and other menstruation-related disorders will move us closer to the goal of personalized care. Furthermore, a deeper mechanistic understanding of menstruation-a fast, scarless healing process in healthy individuals-will likely yield insights into a myriad of other diseases involving regulation of vascular function locally and systemically. We also recognize that many women now delay pregnancy and that there is an increasing desire for fertility and uterine preservation. In September 2018, the Gynecologic Health and Disease Branch of the Eunice Kennedy Shriver National Institute of Child Health and Human Development convened a 2-day meeting, "Menstruation: Science and Society" with an aim to "identify gaps and opportunities in menstruation science and to raise awareness of the need for more research in this field." Experts in fields ranging from the evolutionary role of menstruation to basic endometrial biology (including omic analysis of the endometrium, stem cells and tissue engineering of the endometrium, endometrial microbiome, and abnormal uterine bleeding and fibroids) and translational medicine (imaging and sampling modalities, patient-focused analysis of menstrual disorders including abnormal uterine bleeding, smart technologies or applications and mobile health platforms) to societal challenges in health literacy and dissemination frameworks across different economic and cultural landscapes shared current state-of-the-art and future vision, incorporating the patient voice at the launch of the meeting. Here, we provide an enhanced meeting report with extensive up-to-date (as of submission) context, capturing the spectrum from how the basic processes of menstruation commence in response to progesterone withdrawal, through the role of tissue-resident and circulating stem and progenitor cells in monthly regeneration-and current gaps in knowledge on how dysregulation leads to abnormal uterine bleeding and other menstruation-related disorders such as adenomyosis, endometriosis, and fibroids-to the clinical challenges in diagnostics, treatment, and patient and societal education. We conclude with an overview of how the global agenda concerning menstruation, and specifically menstrual health and hygiene, are gaining momentum, ranging from increasing investment in addressing menstruation-related barriers facing girls in schools in low- to middle-income countries to the more recent "menstrual equity" and "period poverty" movements spreading across high-income countries.
Number: 5
Keywords: amériques; corps; discipline; endométriose; gynécologie; menstruations; médecine; projet charge mentale; régions géographiques; santé; santé des femmes*; santé menstruelle; sciences; thématiques; états-unis

Précarité menstruelle Archives - RQASF (Campagne Rouge #LaVieEnRouge, 2020)
Le Réseau québécois d’action pour la santé des femmes se dédie à travers sa Campagne Rouge #LaVieEnRouge, qui durera 2 ans, à défaire les mythes et les tabous qui entourent les menstruations. Il s’agit d’une campagne participative: nous aurons besoin de vous tou.te.s pour parvenir à un changement global et positif concernant les perceptions et donc le vécu des menstruations… car nous sommes tou.te.s concerné.es! Précarité menstruelle S’engager contre la précarité menstruelle, c’est contribuer à une société plus équitable en favorisant l’accès pour toutes les personnes menstruées aux produits d’hygiène menstruelle. Découvrez la liste de nos partenaires collecteurs et distributeurs, et contactez-nous si vous souhaitez vous aussi vous engager: ensemble, tou.te.s solidaires contre la précarité menstruelle!
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; corps; menstruations; patriarcat; projet charge mentale; précarité menstruelle; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles

Concilier famille et travail dans un horaire atypique ? - Souissi, Takwa (Gazette des femmes, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; charge mentale; conciliation famille-travail; famille; maternité; projet charge mentale; périodes historiques; québec; régions géographiques; santé; thématiques; travail; travail de la construction; travail domestique

Gender-based analysis using existing public health datasets - Tannenbaum, Cara (Canadian Journal of Public Health, 2020)
http://link.springer.com/10.17269/s41997-020-00302-9
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; histoire et politique; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; santé publique; thématiques

Adaptability to social distancing due to COVID-19 and its moderating effect on stress by gender - Zamarripa, Jorge; Delgado-Herrada, Maritza; Morquecho-Sánchez, Raquel; Baños, Raúl; de la Cruz-Ortega, Manuel; Duarte-Félix, Héctor (Salud mental, 2020)
The COVID-19 pandemic, originated in China, has affected millions of people worldwide, leading to various situations such as psychological disorders and diseases that affect people’s physical and mental health, and disrupt their quality of life. Objective. To analyze stress levels during social distancing due to COVID-19 by gender and to determine the moderating effect of adaptability to the situation. Method. The study is cross-sectional and quantitative, with a descriptive-correlational scope. The sample consisted of 1,173 Mexican subjects (522 males [44.5%] and 651 females [22.5%]) with an average age of 25.99 years (DT = 11.19; range = 12 - 77 years). Adaptability and perceived stress were measured, obtaining reliability from appropriate instruments. Results. The results indicated that the greater the number of weeks of social distancing, the higher the perceived level of stress. Also, the better people adapt to social distancing, the less stress occurs. Women were observed to have higher levels of stress compared to men. Discussion and conclusion. The findings highlight the importance of adaptability to the stressful situation of the pandemic, because the effect of severe stress on women largely disappears when there is a high level of adaptability to the event.
Number: 6 https://www.scielo.org.mx/scielo.php?script=sci_arttext&pid=S0185-33252020000600273
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; covid-19; mexique; périodes historiques; ressource en ligne; régions géographiques; santé; santé mentale; stress; thématiques; étude quantitative

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis